Factors Influence Interest in Entrepreneurship Semarang State Polytechnic Student - Nanang Adie Setyawan; Bagus Yunianto Wibowo (Al-Kharaj: Journal of Islamic Economic and Business, 2022)
This study aims to determine the factors that influence interest in entrepreneurship which consists of entrepreneurial mindset, environment and the influence of social media on Semarang State Polytechnic students. Respondents in this study were students of Semarang State Polytechnic with a sample of 100 respondents from the entire population. This study uses a confirmatory factor analysis tool in the SEM of the AMOS 24.0 statistical package. The data collection technique used a questionnaire with incidental sampling and snow ball sampling, namely students who were met and had run entrepreneurship or had participated in entrepreneurship studies and forwarded it to their friends according to the criteria. The results of parameter estimation are consistent with the hypothesis that entrepreneurial mindset significantly influences entrepreneurial interest with a critical ratio (c.r) value of 3.194 and a P-Value of 0.001, Environment has a positive effect on entrepreneurial interest with a critical ratio value (c.r) of 3.179 and a P-Value of 0.001, Social The media has a positive effect on entrepreneurial interest with a critical ratio (c.r) of 4.366 and P-Value ***. The results of this study indicate a positive and significant influence between entrepreneurial mindset, environment, and social media on students' interest in entrepreneurship. Kata Kunci: Minat Berwirausaha, Media Sosial, Pola Pikir Wirausaha, Lingkungan.